The effect of knowledge of ecological concepts and intention to act toward responsible environmental behavior of senior high school students - Ipikasari, Ipikasari; Sigit, Diana Vivanti; Komala, Ratna (International Journal for Educational and Vocational Studies, 2020)
Responsible environmental behavior is one of important factors to protect the environment from damage. Responsible environmental behavior can be built through knowledge of ecological concepts and intention to act toward the environment. This study aims to investigate the effect of knowledge of ecological concepts and intention to act toward responsible environmental behavior of senior high school students. The method used were survey through causal studies and analysis was used path analysis. This study used three variables i.e. ecological concept knowledge (exogenous variable/X1), itention to act (exogenous variable/X2), and environmental responsibility behavior (endogenous variables /X3). The subject were 165 students from grade XI of mathematics and science. The result of hypothesis showed that the path coefficient X1 to X3 was 0,817, X2 to X3 was 0,838, X1 to X2 was 0,832, and X1 to X3 through X2 was 0,70. Knowledge of ecological concepts and intention to act has a direct effect toward responsible environmental behavior of students. Intention to act can be said as the mediated variable between knowledge of ecological and responsible environmental behavior.